Intermittent Training Followed by Detraining Provides the Preservation of Hepatic Tissue and Body Composition of Eutrophic rats in Relation to Obese Rats after the Detraining Period - Barbosa Magalhaes, Alan Jose; Trindade Camargo, Regina Celi [UNESP]; Moreira, Rafael Junges [UNESP]; Seraphim, Patricia Monteiro [UNESP]; Oikawa, Sergio Minoru [UNESP]; Silva Camargo Filho, Jose Carlos [UNESP] (Soc Chilena Anatomia, 2018)
The aim of the study was to evaluate the effects of intermittent training followed by detraining on liver tissue and body composition of rats subjected to a normolipidic or hyperlipidic diet. Sixty Wistar rats were divided into the groups Sedentary Control (SC), Exercised Control (EC), Sedentary Control euthanized at six months of age (SC(6)), Detrained Control (DC), Sedentary Obese (SO), Exercised Obese (EO), Sedentary Obese euthanized at six months of age (SO(6)) and Detrained Obese (DO), which performed intermittent training for eight weeks. After, the groups SC(6), DC, SO(6) and DO performed a detraining protocol for eight weeks. The animals were euthanized, with measurements of body mass and length taken, and retrieval of Epididymal Adipose Tissue (EAT) for body composition variables and the liver for karyometric and stereological analysis. Significant differences were found in the liver mass values of the EC relative to the DO and in the SO(6) liver in relation to all groups, with a greater gain in body mass of the SO(6) in comparison to the EC; in the EAT total, EAT percentage and BM of SO(6) and DO in relation to the EC and the DC and in the karyometric variables of the EC and the DC in relation to EO and DO, with no differences in the stereology and on the Lee index between all groups. Intermittent training showed better effects on the DC liver tissue compared to EO and DO, and on the EC and DC body composition compared to SO(6) and DO.
Keywords: Obesity; Liver; Body Composition; Exercise; Histology